A Molecular Approach to Chronic T-cell Mediated Rejection. (July 2018) - Akalin, Enver
Abstract : Background: Despite the advances in diagnosis of chronic antibody-mediated rejection (AMR), chronic T cell mediated rejection (TCMR) is solely defined by Banff classification as chronic allograft arteriopathy. We hypothesized that T cell-mediated immunity might play a role in interstitial fibrosis and tubular atrophy (IFTA) with Banff inflammation score (i> 0) in non-scarred areas and could be classified as chronic TCMR. Methods: A total of 88 for-cause renal allograft biopsies were studied using Affymetrix HuGene 1.0 ST expression arrays in the following groups; G1(n=16): normal transplant kidney biopsy, G2(n=33): chronic AMR, G3(n=27): chronic TCMR, and G4 (n=12) IFTA without inflammation (i=0). Results: Chronic AMR biopsies (G2) showed significantly increased expression of DSA associates (DSAST), gamma-interferon and rejection (GRIT), cytotoxic T cell (CAT), regulatory T cell (TREG) and constitutive macrophage (CMAT) associated transcripts when compared to normal (G1) biopsies (Table 1). However, chronic TCMR biopsies (G3) had increased intragraft expression CAT and TREG associated transcripts when compared to normal (G1) biopsies. Gene Ontology analysis showed that chronic TCMR biopsies had significant increased expression of gene transcripts related to activation, regulation, and differentiation of T cells, B cells, cytokines, chemokines, chemotaxis, and immune response. There was no significantly increased expression of any pathogenesis based transcripts studied in pure IFTA biopsies (G4). None of the groups had increased expression of endothelial cell associated transcripts (ENDAT). During a median follow-up of 59 months (range, 4 to 85) after the biopsy the graft survival in pure IFTA group (83%) was higher than IFTA with Banff-i group (59%). Chronic AMR group had the lowest graft survival (33%). Figure. No caption available. Conclusion: In summary, we conclude that IFTA biopsies with inflammation in non-scarred areas have a unique molecular signature with increased expression of cytotoxic and regulatory T cells suggesting that it could be classified as chronic TCMR.